IMPLEMENTASI DELAPAN ETNIS TRADISIONAL SUMATERA UTARA PADA MODEL PEMBELAJARAN SENI TERPADU UNTUK MENINGKATKAN APRESIASI DAN KREATIVITAS SISWA DI SD NEGERI 101769 MEDAN TEMBUNG - Putra Afriadi; Mifta Khairina; Phil Ichwan Azhari (Universitas Negeri Medan, 2022)
This study aims to improve students' understanding and creativity in arts and culture subjects. By introducing the arts of eight tribes, students recognize factors such as the participation of 27 students in the city, such as participation in SDN 101769 Class V Medan Tembung. This research uses classroom action research method with two cycles. The results showed that the application of the Integrated Fine Arts Learning Model can increase understanding of traditional cultural arts in the North Sumatra region by introducing art to eight tribes carried out at SD Negeri 101769 Medantenbun City. To increase the understanding and creativity of regional traditional arts and culture, a learning model that can integrate all elements of art and culture can be used, such as, Using an integrated art learning model that has been proven to increase students' understanding of art subjects.